2018
DOI: 10.1038/s41598-018-34962-y
|View full text |Cite
|
Sign up to set email alerts
|

The two phases of the Cambrian Explosion

Abstract: The dynamics of how metazoan phyla appeared and evolved – known as the Cambrian Explosion – remains elusive. We present a quantitative analysis of the temporal distribution (based on occurrence data of fossil species sampled in each time interval) of lophotrochozoan skeletal species (n = 430) from the terminal Ediacaran to Cambrian Stage 5 (~545 – ~505 Million years ago (Ma)) of the Siberian Platform, Russia. We use morphological traits to distinguish between stem and crown groups. Possible skeletal stem group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 97 publications
2
51
0
Order By: Relevance
“…Since then, a long history of body plan modifications, reversals, and convergences has obscured the relationships among some animal lineages 2 . Understanding the genomic toolkit that enabled innovations in skeletons and armour is critical to reconstructing the early radiation of major clades 3,4 . In particular, Lophotrochozoa (including annelids, brachiopods, molluscs and others) presents a significant and unresolved problem for phylogenetic reconstruction, and controversies over the affinities of key fossils 5 .…”
mentioning
confidence: 99%
“…Since then, a long history of body plan modifications, reversals, and convergences has obscured the relationships among some animal lineages 2 . Understanding the genomic toolkit that enabled innovations in skeletons and armour is critical to reconstructing the early radiation of major clades 3,4 . In particular, Lophotrochozoa (including annelids, brachiopods, molluscs and others) presents a significant and unresolved problem for phylogenetic reconstruction, and controversies over the affinities of key fossils 5 .…”
mentioning
confidence: 99%
“…Global diversity in the early Palaeozoic began with an initial radiation during the first 20 million years of the Cambrian., commonly known as the "Cambrian Explosion" (Sepkoski, 1979;Zhu et al, 2006;Bambach et al, 2007;Servais et al, 2008) occurring within two distinct phases, separated by significant environmental and biotic events (Zhuravlev and Wood, 2018). Despite the evident proliferation of life, two critical intervals of major genera-level losses and taxonomic turnover appear in apparent synchrony with the Kalkarindji (Zhuravlev and Wood, 1996;Faggetter et al, 2017).…”
Section: Biotic Instabilitymentioning
confidence: 99%
“…Extended intervals of marine anoxia are often associated with warmer ocean temperatures due to the diminished capacity for warmer water to store dissolved oxygen (Hough et al, 2006). Records of warm sea surface temperatures (Wotte et al, 2019), a global greenhouse climate (Hearing et al, 2018;Zhuravlev and Wood, 2018) and potential global warming indicated by deposition of extensive carbonate and evaporite deposits (Keller et al, 2012;Schmid, 2017) are evident during the window of time for the Kalkarindji emplacement. During this period of the spread of ocean anoxia may have rendered shallow marine environments potentially vulnerable to CH4 and/or H2S poisoning during transgression.…”
Section: Environmental Instabilitymentioning
confidence: 99%
“…The Cambrian Explosion is distinguished by the apparent origination of bilaterian body plans, essentially phyla, the endemism of its biotas and a dominance in many faunas of predators. The explosion was partitioned by the Sinsk extinction event, at least in Siberian sections (Zhuravlev & Wood, 2018); prior to the event many stem groups radiated but few survived, while crown group brachiopods and molluscs diversified. A critical part of the 'explosion' was the Cambrian substrate revolution (Bottjer et al 2000).…”
Section: Key Early Palaeozoic Biodiversity and Extinction Eventsmentioning
confidence: 99%